IMPROVING CHILDREN’S ENGLISH SKILLS BY USING LINGOKIDS APP - Tjut Dwi Anggraini Damcha; Erna Budiarti (Institut Pendidikan Tapanuli Selatan, 2022)
The rapid development of technology and industry had influenced the learning capacity of childhood education. The childhood education is also adjusting to the revolution. Thus, a lot of learning media are created to meet the needs of learning process. The use of mother language in daily life alongside the foreign languages especially English language. One of childhood’s characteristic is they can easily absorb the sounds of foreign language they heard and see around them. Unfortunately, it’s often occurred that their ability wasn’t supported with the right guidance by their surroundings, so they can’t interpret the sounds they heard, but only repeated the sounds. They needed a suitable learning media and method to stimulate their language ability. One of digital learning media based of an app is called LingoKids app. LingoKids app is a playlearning™ app for children between the ages of 2 to 8 years old.LingoKids app is a learning media that researcher used in this research to optimizing English language ability in childhood education. The result showed that LingoKids can help improve early childhood English skills and is suitable for application with a variety of learning strategy.